41 shots ... and counting: what Amadou Diallo's story teaches us about policing, race and justice - Roy, Beth (Syracuse studies on peace and conflict resolution, 2009)
Introduction: the tragedy of Amadou Diallo -- Defining the question : in the courtroom -- Defining the question : in the street -- Defining the question : in the community -- Policing the boundaries : in the precinct house -- Policing and politics : in city hall -- Seeking answers beyond Diallo -- Coloring manhood in shades of violence -- Underworld and overworld -- Remedies and realism -- Diallo's challenge : making the just society